2019
DOI: 10.1002/ptr.6298
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol reduces the expression of insulin‐like growth factor‐1 and hepatocyte growth factor in stromal cells of women with endometriosis compared with nonendometriotic women

Abstract: Resveratrol, a phytoalexin polyphenol, has antiproliferative, antiangiogenic, antiinflammatory, and antioxidant properties. The present study has assessed the effect of resveratrol treatment on the expression of insulin-like growth factor-1 (IGF-1) and hepatocyte growth factor (HGF) in endometrial stromal cells (ESCs) from women with and without endometriosis. Endometrial tissues were obtained from 40 endometriotic patients and 15 nonendometriotic control women. After the enzymatic digestion, 13 eutopic ESCs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 53 publications
(66 reference statements)
6
46
2
Order By: Relevance
“…Increased HGF expression has been shown in ectopic compared to eutopic endometrial tissue in patient with endometriosis [43] or non-endometriotic patients [53]. Regarding ESCs, one study showed increased HGF protein expression in EuESCs compared to CESCs [54] and in line with our findings, in a study by Arablou et al HGF gene expression was higher in EESCs compared to EuESCs [55].…”
Section: Discussionsupporting
confidence: 90%
“…Increased HGF expression has been shown in ectopic compared to eutopic endometrial tissue in patient with endometriosis [43] or non-endometriotic patients [53]. Regarding ESCs, one study showed increased HGF protein expression in EuESCs compared to CESCs [54] and in line with our findings, in a study by Arablou et al HGF gene expression was higher in EESCs compared to EuESCs [55].…”
Section: Discussionsupporting
confidence: 90%
“…Resveratrol is considered to be effective in preventing and treating endometriosis. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 In the present study, we showed that resveratrol inhibited the proliferation, migration, and invasion of ESCs in cell cultures ( Figures 4 A, 4C, and 4E) and suppressed the growth of ectopic endometrium in the mouse endometriosis model ( Figure 7 B). Then, we demonstrated that resveratrol decreased MTA1 expression and suppressed EMT induced by MTA1-ZEB2 in endometrial cells ( Figure 3 G) and endometriosis mice ( Figures 7 C and 7D).…”
Section: Discussionsupporting
confidence: 59%
“…Since EMT is involved in the pathogenesis of endometriosis, 2 , 22 , 23 , 24 , 25 , 26 , 27 , 28 we measured the expression of E-cadherin, an epithelial marker, and vimentin, a mesenchymal marker, by western blotting, and revealed lower E-cadherin expression and higher vimentin as well as MTA1 expression in EcESCs than those in NESCs ( Figures 3 A and 3D). Moreover, in a mouse endometriosis model, vimentin expression was higher and E-cadherin expression was lower in ectopic tissues than in eutopic tissues in IHC ( Figure 1 F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study, various concentrations of resveratrol (Sigma-Aldrich) (12.5, 25, 50, 100, 200 and 400 µmol/L) were tested to find safety dose of resveratrol by MTT assay, 17 based on MTT assay findings, 16 with EuESCs and CESCs (P < .01-<.0001; P < .0001; and P < .05-<.001, respectively). RANTES protein expression was also higher in…”
Section: Determining the Appropriate Concentration For Treatment Ofmentioning
confidence: 99%